Attitude, Practice and Preparedness of Dental Practitioners for Providing Oral Care to Patients with Speech and Hearing Impairment - Khansa Rafi; Syed Masood-; Saba Tabassum (University of Lahore, 2024)
Objective: To explore the attitudes, practices and preparedness of dental practitioners for providing oral care to patients with speech and hearing impairment. Methodology: This cross-sectional study was conducted on a sample of 467 dental practitioners between November 2021 and April 2022. A survey questionnaire was administered to practicing dental practitioners in Pakistan through online Google forms and in person. The survey included questions regarding dentists' demographic information, their attitudes and concerns, practices and views regarding training needs concerning the provision of oral care to patients with speech and hearing impairment. Data was analyzed with STATA version 16. Descriptive statistics with frequencies were computed and x² was used to find out the associations between different variables. Results: The findings suggest that a significant proportion of participants, specifically 88.22%, were unfamiliar with sign language and relied on the assistance of an attendant (54.82%) for communication purposes. According to their accounts, surgical extraction (54.4%) was perceived as the most challenging treatment to execute, whereas scaling and polishing (73.9%) was considered the easiest treatment  to administer in this particular population. When it came to providing care for individuals with speech and hearing impairment, several barriers were identified. These included communication obstacles (65.3%), patient cooperation (63.2%), concerns about medical emergencies (29.1%), inadequately trained staff (26.3%), and limited experience (25.5%). The participants unanimously agreed that there is a pressing need for enhanced undergraduate training (43.68%). Additionally, they suggested that it should be obligatory for students to treat a specific number of patients with speech and hearing impairment as part of their undergraduate training (49.25%). Conclusion: There is a need to address the identified barriers and create a better understanding between dentists and individuals with speech and hearing im- pairments. Basic dental signs should be learned and mastered to engage patients more effectively via non-verbal communication.